Perbedaan Tingkat Moral Siswa Antara Sekolah Berbasis Islam Dengan Sekolah Umum - Utama Yoga, Okta, Setiyo Purwanto, S.Psi. M.Si, Dr. Mutohharun Jinan,M.Ag (2016)
Every school has a very large role in developing student's potential develop it self by having spiritual power of Religion, Self Development, Personality, Intelligence, noble morality and skils requid him self and the community, in the Nation and State. Beside that, the essence of school education to develop students' potential, namely the intellectual, social skills, and religiosity. some things that can affect the moral development of the students, such as school, peers, and community. according to the functions and roles, between Morality and Akhlaq of the same, therefore schools need to instill good morals to students with an Islamic education where the learning there are substantially directed learners have good moral in everyday life, with student's Formation who have good Morality, will more easily provide insight or religious teachings to children in order to know the good and bad things not only behavior but behavior momentary permanent. The purpose of this research: to know the difference between the moral level of Islamic-based schools with public schools. the proposed hypothesis is no difference between Islam schools with school-based General. subjects in this study were 160 students, this study uses research-based study purposive random sampling until investigators determine the type based on the characteristics. data collection tools in this study using a scale of moral level. Data analysis techniques using test Independent Sample T-Test. The analysis results obtained from this study are: there are significant differences between the Islamic-based schools with public schools, Islamic-based School has a mean of 87.31, while for Public-based School have a mean 84.60. Islamic-based schools is The Moral level higher than the general school. keywords: moral level, Islam-based schools, public schools